The results of microbiological monitoring for bacterial pathogens of the respiratory tract in children in 2017 - G.O. Lezhenko; O.E. Pashkova (Zaslavsky O.Yu., 2018)
The article presents the results of bacteriological monitoring of 483 children aged 3 to 14 years with acute respiratory diseases in Zaporizhzhia and Zaporizhzhia region in 2017. It was found that leading pathogens were Streptococcus pneumoniae (49.4 %) and bacteria of the genus Haemophilus (36.2 %) in the presence of bacterial respiratory infection. The analysis of the antibiotic susceptibility patterns showed that the microorganisms demonstrated the highest sensitivity to the third-/fourth-generation cephalosporins, vancomycin, linezolid and levofloxacin. There was noted a high antibiotic resistance of Streptococcus pneumoniae to penicillins (56 % of strains), clindamycin (43 % of strains) and erythromycin (45 % of strains). The isolates of bacteria of the genus Haemophilus most often showed resistance to the ampicillin (58.1 % of strains) and protected penicillins (52 % of strains). On the basis of obtained data, there was substantiated the expediency of using cefpodoxime proxetil, the third-generation cephalosporin, as the starting antibacterial drug in the therapy of acute bacterial respiratory infection in children.